Hey!
--------------------------------------------
Solution:
Remember to follow PEMDAS.
= (68 * 95) + 90 / 10
= (6,460) + 90 / 10
= 6,460 + 9
= 6,469
--------------------------------------------
Answer:
6,469
--------------------------------------------
Hope This Helped! Good Luck!
In order to find the answer to the question you will have to use PEMDAS and then solve.
[tex](68\times95)+90\div10[/tex]
Using PEMDAS:
[tex]68\times95=6460[/tex]
[tex]6460+90\div10[/tex]
[tex]90\div10=9[/tex]
[tex]6460+9[/tex]
[tex]6460+9=6469[/tex]
[tex]=6469[/tex]
Therefore your answer is "6469."
Hope this helps.
Simplify these expression a.-8p + (-9p)+(-2p) b. -3jk+5jk+(-6jk)
Step-by-step explanation:
Combine like terms
a. -8p + (-9p) + (-2p) = -8p -9p -2p = (-8 - 9 - 2)p = -19p
b. -3jk + 5jk + (-6jk) = -3jk + 5jk - 6jk = (-3 + 5 - 6)jk = -4jk
Terms are called "like terms" if they have the same variable part (the same letters in the same powers). Like terms differ at most coefficient.
Answer:
a. –8p + (–9p) + (–2p)
Combine the coefficients of the like monomials.
[(–8) + (–9) + (–2) = –19]
Answer: –19p
b. –3jk + 5jk + (–6jk)
Combine the coefficients the like of monomials.
[(–3) + 5 + (–6) = –4]
Answer: –4jk
Step-by-step explanation:
straight from Penn
50 Point Question...
A dog owner observes that from birth to age 14 weeks, the puppy’s weight can be modelled by the equation w = 365×(1.23)t (0 ≤ t ≤ 14),
(1) Write down the scale factor, and use this to find the percentage increase in the weight each week.
(2) Use the law of logs to find the age at which the puppy will weigh 4000 grams
Answer:
See explanation
Step-by-step explanation:
A dog owner observes that from birth to age 14 weeks, the puppy’s weight can be modelled by the equation
[tex]w = 365\cdot (1.23)^t \ (0\le t \le 14)[/tex]
In this equation,
number 365 represents the initial weight of puppy;number 1.23 can be rewritten as 1+0.23, where 0.23 (or 23%) is the rate of weight increase.When w=4,000, then
[tex]4,000=365\cdot (1.23)^t\\ \\(1.23)^t =\dfrac{4,000}{365}=\dfrac{800}{73}\\ \\t=\log_{1.23}\dfrac{800}{73}\approx 11.5651[/tex]
This means that puppy will weight 4,000 grams nearly at the middle between 11th week and 12th week.
PLEASE HELP The function f(x) = x2 − 2x + 8 is transformed such that g(x) = f(x − 2). Find the vertex of g(x).
(1, 5)
(3, 7)
(1, 9)
(−1, 7)
Answer: Second option.
Step-by-step explanation:
Given the function f(x):
[tex]f(x) = x^2 - 2x + 8[/tex]
Find [tex]f(x -2)[/tex]:
[tex]f(x -2)=(x-2)^2 - 2(x-2) + 8[/tex]
Remember that:
[tex](a\±b)^2=a^2\±2ab+b^2[/tex]
Then, simplifying:
[tex]f(x -2)=x^2-2(x)(2)+2^2 - 2x+4+ 8\\\\f(x-2)=x^2-6x+16[/tex]
So the function g(x) is:
[tex]g(x)=x^2-6x+16[/tex]
Use the following formula to find the x-coordinate of the vertex of g(x):
[tex]x=\frac{-b}{2a}[/tex]
In this case:
[tex]a=1\\b=-6[/tex]
Then:
[tex]x=-\frac{-(-6)}{2(1)}=3[/tex]
Substitute this value into the function g(x) in order to find the y-coordinate of the vertex. Since [tex]g(x)=y[/tex], you get:
[tex]y=3^2-6(3)+16=7[/tex]
Therefore, the vertex of g(x) is:
[tex](3,7)[/tex]
Answer:
Second one
Step-by-step explanation:
There are two boxes, one has a dimension of 6x2x3 and the other has dimension of 2x3x6. Which is bigger?
1. f(x) = 5x +4
for Range = {5, 6, 7, 8}
Determine the domain
Answer:
see explanation
Step-by-step explanation:
Given the range of f(x), find the domain by equating f(x) to each of the values in the range, that is
5x + 4 = 5 ( subtract 4 from both sides )
5x = 1 ( divide both sides by 5 )
x = [tex]\frac{1}{5}[/tex]
5x + 4 = 6 ( subtract 4 from both sides )
5x = 2 ( divide both sides by 5 )
x = [tex]\frac{2}{5}[/tex]
5x + 4 = 7 ( subtract 4 from both sides )
5x = 3 ( divide both sides by 5 )
x = [tex]\frac{3}{5}[/tex]
5x + 4 = 8 ( subtract 4 from both sides )
5x = 4 ( divide both sides by 5 )
x = [tex]\frac{4}{5}[/tex]
Thus
domain = { [tex]\frac{1}{5}[/tex], [tex]\frac{2}{5}[/tex], [tex]\frac{3}{5}[/tex], [tex]\frac{4}{5}[/tex] }
3/8 multiplied by 4/5 in fraction form
I WILL GIVE BRAINLIEST
3/8 multiplied by 4/5 forms the fraction 3/10
What is the required fraction ?
A fraction has numerator in top & denominator in bottom.
Given fractions are 3/8 & 4/5.
To multiply these two numbers, we have to multiply numerator of 3/8, i.e. 3 with numerator of 4/5, i.e. 4.
Also we have to multiply denominator of 3/8, i.e. 8 with denominator of 4/5, i.e. 5.
So, the new number be 3/8 × 4/5
= (3×4)/(8×5)
= 12/40 = 3/10
The required fraction is 3/10
Learn more about fraction here :
https://brainly.com/question/78672
#SPJ2
The average mass of a grain of sand on a beach is about 0.000015. What is 0.000015 in scientific notation ?
Answer:
15*10∧-5
Multiple 15 x 0,000001 = 0,000015.
You have already 5 miles of an 18 -miles trail. If you walk the rest of the rest of the trail at a pace of 1 mile in 17 minutes, How many wile it take you to finish the trail?
To finish the remainder of the 18-mile trail, it will take 3 hours and 41 minutes at a pace of 1 mile in 17 minutes.
Explanation:To find out how many miles it will take to finish the trail, subtract the distance already covered from the total length of the trail. In this case, subtract 5 miles from 18 miles to get 13 miles remaining. Next, divide the remaining distance by the pace at which you walk, which is 1 mile in 17 minutes. So, if it takes 17 minutes to walk 1 mile, it will take 17 times 13 minutes to finish the rest of the trail. Finally, calculate the total time in minutes by multiplying: 17 times 13 equals 221 minutes, or 3 hours and 41 minutes to finish the trail.
Learn more about Calculating time and distance here:https://brainly.com/question/32817533
#SPJ2
Solve for r.
K = 8r-s
To solve for r in the equation K = 8r - s, add s to both sides of the equation and divide both sides by 8, resulting in r = (K + s)/8.
Explanation:To solve for r in the equation K = 8r - s, we need to isolate r.
We can start by adding s to both sides of the equation to get K + s = 8r.
Then, we divide both sides by 8 to solve for r.
The final equation is r = (K + s)/8.
Find the absolute value l-7 -9il
spends 2 hours and 20 minutes trading stickers and 125 minutes doing homework. What activity does he spend more time on? How much more time?
If the perimeter of International Space Station Base, which is rectangular in shape, is 720 cm and its length is 120cm, find the area of the International Space Station Base.
Answer:
Area = 28800 cm².
Step-by-step explanation:
Given : If the perimeter of International Space Station Base, which is rectangular in shape, is 720 cm and its length is 120cm,
To find : find the area of the International Space Station Base.
Solution : We have given
Perimeter = 720 cm .
Length = 120 cm .
Perimeter = 2 ( length + width ) .
Plugging the values
720 = 2 ( 120 + width )
On dividing both sides by 2
360 = 120 + width .
On subtracting both sides by 120.
240 cm = width.
Area = length * width .
Area = 120 * 240 .
Area = 28800 cm².
Therefore, Area = 28800 cm².
the vet put 2 litters of kittens in a cage with 5 other kittens she also put 3 litters of puppies in the cage next door with one other puppy if all the litters have the same number of animals and the cages now contain the same number of animals how many animals are in each litter
answer:
10
Step-by-step explanation:
if u add 5+3+2 that will equal 10
Each litter contains 4 animals.
Explanation:To find the number of animals in each litter, we need to use the given information. We know that the vet put 2 litters of kittens in a cage with 5 other kittens, so there are a total of 7 kittens in the first cage. In the second cage, there are 3 litters of puppies with 1 other puppy, so there are 4 puppies in the second cage. Since the cages now contain the same number of animals, we can set up an equation: 2 litters of kittens + 5 other kittens = 3 litters of puppies + 1 other puppy. Substituting the given numbers, we have 2x + 5 = 3x + 1, where x represents the number of animals in each litter. Solving this equation, we find that x = 4. Therefore, each litter contains 4 animals.
Factor the following polynomial completely 6x^5-30x^4-84x^3
Answer:
6x^3(x+2)(x-7)
Step-by-step explanation:
1st step: factor out common term, 6x^3(x^2 - 5x - 14)
2nd step: Factor x^2 - 5x - 14, (x + 2)(x - 7)
3rd step: simplify, 6x^3(x+2)(x-7)
I am joyus to assist :)
2- + (2+7) Use number properties to simplify the following expression
Answer:
-7.
Step-by-step explanation:
2- + (2+7)
First work out the parentheses ( by order of operations PEMDAS)
= 2 - + 9
= 2 - 9 (as - + = -)
= -7.
the question is y³+9y²
Rocky simplified an expression in three steps, as shown:
x to the power of negative 5 multiplied by y to the power of 2, over y multiplied by x to the power of 3 multiplied by x to the power of 3 multiplied by y to the power of negative 5, the whole to the power of 2 equals x to the power of negative 10 multiplied by y to the power of 4, over y to the power of 2 multiplied by x to the power of 6 multiplied by x to the power of 6 multiplied by y to the power of negative 10 equals x to the power of negative 10 multiplied by y to the power of 4, over y to the power of negative 8 multiplied by x to the power of 12.
Which is the first incorrect step and why?
Step 1, all the exponents are increased by 2
Step 1, all the exponents are multiplied by 2
Step 2, the exponents in the denominator are added during multiplication
Step 3, the exponents of the same base are added during division
Answer:
Step three is wrong because when you divide use the quotient rule which is in division the exponents are subtracted and in this problem the exponents are added
Answer:
Step 3.
Step-by-step explanation:
The given expression is
[tex](\frac{x^{-5}y^2}{yx^3\cdot x^3y^{-5}})^2[/tex]
Step 1: Using distributive property of exponent we get
[tex]\frac{(x^{-5})^2(y^2)^2}{(y)^2(x^3)^2\cdot (x^3y^{-5})^2}[/tex] [tex][\because (ab)^x=a^xb^x][/tex]
[tex]\frac{x^{-10}y^4}{y^2x^6\cdot x^6y^{-10}}[/tex]
Ste 2: Using product property of exponent, we get
[tex]\frac{x^{-10}y^4}{y^{2-10}x^{6+6}}[/tex] [tex][\because a^ma^n=a^{m+n}][/tex]
[tex]\frac{x^{-10}y^4}{y^{-8}x^{12}}[/tex]
Step 3: Using quotient property of exponent, we get
[tex]x^{(-10-12)}y^{4-(-8)}[/tex] [tex][\because \frac{a^m}{a^n}=a^{m-n}][/tex]
[tex]x^{(-22)}y^{12}[/tex]
Therefore, the first incorrect step is 3.
What are the coordinates of point B on the pre-image
Answer: C)- (2,3)
Answer on edge
Which type of fruit has a cost $1.20 per pound?
Answer:
Apples
Step-by-step explanation:
Answer: Apples cost $1.20 per pound of apples.
Step-by-step explanation:
6/5 = 1.20 per pound of apples
4/5 = 0.80 per pound of bananas
5/4 = 1.25 per pound of peaches
9/6 = 1.50 per pound of kiwis
Help me please I got 55 questions to go in I’m not really good at math
Answer:2 hr 30 min
Step-by-step explanation:
Answer:
D) 2 hr 30 min
Step-by-step explanation:
The current time on the clock says 6:30 pm. Sherry's mom says that she must go to bed at 9:00 pm. Note that there are 60 minutes in an hour. Subtract:
9:00 pm = 8:60 pm
Subtract:
8:60 pm - 6:30 pm = 2:30
2 hours 30 minutes is your answer, or D).
~
find the area of a triangle with a base of 8 cm and a height of 10 cm
Answer:
A = 40 cm²Step-by-step explanation:
The formula of an area of a triangle:
[tex]A_\triangle=\dfrac{b\cdot h}{2}[/tex]
b - base
h - height
We have b = 8cm, h = 10cm.
Substitute:
[tex]A=\dfrac{(8)(10)}{2}=\dfrac{80}{2}=40\ (cm^2)[/tex]
If g(x) = x2 − 4, find g(5).
6
14
21
29
plz help!!
Answer: 21
Step-by-step explanation: 5*5=25-4=21
To find g(5), substitute the value of x as 5 in the function g(x) = x^2 - 4. Then, calculate the result to obtain g(5) = 21.
Explanation:Given, the value of x is 5 and a function g(x) = x^2 - 4. To find g(5), we need to substitute the value of x as 5 in the function g(x) = x2 - 4.
So, on substituting the value of x, the answer becomes g(5) = 52 - 4. Here, 52 is the square of
On Calculating further, g(5) = 25 - 4 = 21.
Therefore, g(5) = 21. The answer obtained is 21.
Learn more about Function evaluation here:https://brainly.com/question/12056604
#SPJ2
18. Convert 9.268 to a fraction, the 6 and 8 are repeating
we'll start off by making the recurring decimal value to a variable, hmmm say "x", thus x = 9.268686868......
we'll next multiply that value by a power of 10 so that the recurring decimal part moves over to the left of the decimal point, the recurring decimals in this case are "68", but we need to bring the 2 in front along as well, so to move all those three fellows, we'll need 1000.
we'll next multiply the same value by a power of 10 that brings two of the recurring decimals over, so 1000 gives us one "68" over, we'll need "6868" over to the left, so we'll use 100000, let's proceed.
[tex]\bf x = 9.2\overline{68}\qquad \qquad \begin{array}{llll} 1000\cdot x&=&9268.\overline{68}\\\\ 100000\cdot x&=&926868.\overline{68} \end{array}~\hfill \begin{array}{rllll} \stackrel{100000x}{926868.\overline{68}}\\\\ -\stackrel{1000x}{9268.\overline{68}}\\ \cline{1-1}\\ 917600.00 \end{array} \\\\\\ 100000x-1000x = 917600\implies 99000x=917600 \\\\\\ x = \cfrac{917600}{99000}\implies x = \cfrac{4588}{495}[/tex]
2 3/4 to a decimal terminating or repeating
Answer: Terminating decimal
Step-by-step explanation:
2 3/4 as a faction is 2.75
2.75 is a terminating decimal
Find the value of x
Answer: x=58
Step-by-step explanation:
We know that the entire angle equals 360 degrees
Let’s subtract 293 from 360
360- 293 = 67
Then let’s subtract 44 from 67 to get (x-35)
67 - 44 = 23
We now know that 23 = (x - 35), so let’s write and solve the equation for it
23 = x-35
Add 35 on each side
X = 58
72% and 89% confirm that the mean theses two are scores is 80.5%
Answer:
correct. the mean of 72 and 89 is 80?5
Step-by-step explanation:
find the mean to confirm it.
(a+b)/2
72+89= 161
161/2=80.5
7
factors of 56
What are factors of 56
Answer: 1 , 2 , 4 , 7 , 8 , 14 , 28 , 56
Step-by-step explanation:
Answer:
1 , 2 , 4 , 7 , 8 , 14 , 28 , 56
Step-by-step explanation:
please mark me brainiest and like and rate 5 stars
Write and solve an equation
based off the verbal phrase.
6 more than x is equal to 33
x + 6 = 33 ---> is 6 more than x ^^
x = 27
which fraction is equivalent to 3?
Mistake in the Question:
The number 3 is not a fraction.
Answer:
Suppose if it is 3/8 then do the following:
Multiply
3
__ by an equivalent fraction that equals 1.
8
An equivalent fraction is equal to 1 such as 2 or 3
__ __
2 3
An equivalent fraction is the same as multiplying by 1 so the ratio does not change.
This fraction would be equal to a where a is an integer.
__ = 1
a
Hence an example would be that
2 3 6
__ . __ = __
2 8 16
Request: Please mark me as the brainliest.
Factor 2X4 - 20x2 - 78.
Answer:
-110 = -2^1×5^1×11^1
Step-by-step explanation:
Factor the following integer:
-110
Hint: | Is 110 divisible by 2?
The last digit of 110 is 0, which means it is even. Therefore 110 is divisible by 2:
110 = 2 55:
-110 = -2×55
Hint: | Now try to factor 55. Is 55 divisible by 2?
55 is not divisible by 2 since 55 is odd and 2 is even:
-110 = -2×55 (55 is not divisible by 2)
Hint: | Is 55 divisible by 3?
The sum of the digits of 55 is 5 + 5 = 10, which is not divisible by 3. This means 55 is not divisible by 3:
-110 = -2×55 (55 is not divisible by 2 or 3)
Hint: | Is 55 divisible by 5?
The last digit of 55 is 5, which means 55 is divisible by 5:
55 = 5 11:
-110 = -2×5×11 (11 is not divisible by 2 or 3 since 55 is not)
Hint: | Now try to factor 11. Is 11 divisible by 5?
The last digit of 11 is not 5 or 0, which means 11 is not divisible by 5:
-110 = -2×5×11 (11 is not divisible by 2, 3 or 5)
Hint: | Is 11 divisible by 7?
Divide 7 into 11:
| | 1 | (quotient)
7 | 1 | 1 |
- | | 7 |
| | 4 | (remainder)
11 is not divisible by 7:
-110 = -2×5×11 (11 is not divisible by 2, 3, 5 or 7)
Hint: | Is 11 prime?
No primes less than 11 divide into it. Therefore 11 is prime:
-110 = -2×5×11
Hint: | Express -110 as a product of prime powers.
There is 1 copy of 2, 1 copy of 5 and 1 copy of 11 in the product:
Answer: -110 = -2^1×5^1×11^1